PHYTOCHEMICAL STATUS, ANTIBACTERIAL ACTIVITY AND ANTIOXIDANT PROPERTY OF DATURA METEL L. - Krishnan, Jithu U.; George, Meera; G., Ajesh (International Journal of Current Pharmaceutical Research, 2017)
Objective: Medicinal plants are a source of great economic value all over the world and are on the front dusk of traditional medicine. Daturametel L, is one among the foresaid and this plant can be explored further as per its diversity of uses and on the basis of wide range of chemical compounds reported to be present in various parts of the plant. In the present investigation, Phyto-chemistry of D. metel has been analysed along with its antibacterial property. Methods: The selected plant leaves were collected and powdered. The bioactive compounds were extracted by using different solvents. Various phytochemical tests for alkaloids, flavonoids, saponins, steroids, terpenoids, tannins, glycosides and amino acids were done accordingly with standard protocol of testing. The study also extends to view the anti-bacterial potential by determining inhibition of growth using agar well diffusion method. Results: Phytochemical analysis reflected the presence of compounds like alkaloids, flavonoids, saponins, tannins, glycosides, and amino acids. It was noted that steroids and tannins are absent. Antimicrobial activity proves extract of ethanolis the most promising against the pathogens from the rest screened. Conclusion: Thearticle addresses, the undocumented knowledge regarding the phytochemical profile of D. metel which demand further exploration widely to serve Humanity. Antimicrobial potential of ethanol extract are very promising to deliver it as a pharmaceutical.